2019
DOI: 10.1088/1755-1315/394/1/012037
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Analysis of Land in Forest Peat Swamp in Resort Pondok soar, Tanjung Puting National Park, Central Kalimantan

Abstract: Peatlands are ecosystems with the particular characteristic that is high organic matter content. On the other hand, these features lead to the peat soil vulnerable to decreasing the quality of the land. This study aimed to analyze the physical and chemical properties of peat soil in the peat swamp forest in the Resort Pondok soar, Tanjung Puting National Park in Central Kalimantan. The method used in this research is systematic sampling with a set of five points as soil sampling with twice replications within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 2 publications
1
7
0
Order By: Relevance
“…The pH of an aqueous solution extracted from Jiffy pot was lower than the other studied pots, this is because the Jiffy pot used in this study is made of Sphagnum peat moss and wood pulp. The pH result observed commensurate with the pH range of peat soil of 3.7–5.2 with an average pH of 4.5 [ 44 ]. After 7 days of incubating the dishes with seeds, the SG and the RSG for all the seeds tested from the four saturated aqueous pot extracts were 100%.…”
Section: Resultssupporting
confidence: 58%
“…The pH of an aqueous solution extracted from Jiffy pot was lower than the other studied pots, this is because the Jiffy pot used in this study is made of Sphagnum peat moss and wood pulp. The pH result observed commensurate with the pH range of peat soil of 3.7–5.2 with an average pH of 4.5 [ 44 ]. After 7 days of incubating the dishes with seeds, the SG and the RSG for all the seeds tested from the four saturated aqueous pot extracts were 100%.…”
Section: Resultssupporting
confidence: 58%
“…hominissuis is most commonly found in peat bogs and sphagnum and this environment is regarded as a reservoir for this NTM [ 164 ]. The pH of this environment is typically around 4.5 and presumably this NTM is well adapted to this low pH [ 165 ].…”
Section: Conditions For Survival and Multiplication Of Mycobacteria I...mentioning
confidence: 99%
“…Ash content of Kinali peat soil was significantly different among land use types (Figure 10). It was inversely related to fiber content [17]. They found that ash content of Tanjung Soar, Kalimantan, peat soil (20 ->400 cm depth) was 1.13-43.88%.…”
Section: Soil Physical Characteristicsmentioning
confidence: 98%